Endgame ebook Inside the royal family and the monarchy's fight for survival. - Scobie, Omid (2023)
***The Instant New York Times Bestseller*** Endgame, the explosive book from longtime royal journalist Omid Scobie and author of the international blockbuster Finding Freedom, is a penetrating investigation into the current state of the British monarchy—an unpopular king, a power-hungry heir to the throne, a queen willing to go to dangerous lengths to preserve her image, and a prince forced to start a new life after being betrayed by his own family. Queen Elizabeth II's death ruptured the already-fractured foundations of the House of Windsor—and dismantled the protective shield around it. With an institution long plagued by antiquated ideas around race, class and money, the monarchy and those who prop it up are now exposed and at odds with a rapidly modernizing world. Relying on his vast experience as a royal reporter and over a decade of conversations and interviews with current and former Palace staff, trusted friends of the royals and even the family members themselves, Scobie pulls back the curtain on an institution in turmoil to show what the monarchy must change in order to survive. This is the monarchy's endgame. Do they have what it takes to save it?